Estimating the Impact of Trade and Offshoring on American Workers using the Current Population Surveys - Ebenstein, Avraham; Harrison, Ann; McMillan, Margaret; Phillips, Shannon (The Review of Economics and Statistics, 2014)
We link industry-level data on trade and offshoring with individual-level worker data from the Current Population Surveys from 1984 to 2002. We find that occupational exposure to globalization is associated with significant wage effects, while industry exposure has no significant impact. We present evidence that globalization has put downward pressure on worker wages through the reallocation of workers away from higher-wage manufacturing jobs into other sectors and other occupations. Using a panel of workers, we find that occupation switching due to trade led to real wage losses of 12 to 17 percentage points.